Генологічні модифікації української поетологічної лірики - Артеменко, Людмила Вікторівна; Artemenko, Liudmyla (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті на матеріалі поетичних текстів української поетологічної лірики ХІХ–ХХ ст. проаналізовано жанри неканонічного типу, у яких авторська комунікативна стратегія слугує для спрямування читача на певні генологічні зіставлення та паралелі з окремими більш або менш традиційними жанровими побудовами.The present article is concerned with investigation of the specificity of the genre of the Ukrainian poetological lyrics. In the present study the poetological lyrics is described as having the thematic scope, defined by the range of the issues, related to the artistic reflections or the self-reflections, the introspection of the author. Based on the poetic texts of the Ukrainian poetological lyrics of the ХІХ – ХХ centuries, the genres of the non-canonical type have been analyzed, in which the author’s communicative strategy serves for leading the reader to the certain genological comparison and parallelizing between the independent genre constructions, more or less traditional. Generally, five genological types are relegated to the genres of the non-canonical type of Ukrainian poetological lyrics: 1) the martyrological lyrics; 2) the lyrical portrait or self-portrait; 3) the travel notes; 4) the versified poetics; 5) the monument (memorial).
Genological Modifications of Ukrainian Poetological Lyrics
Keywords: поетологічна лірика; жанрова специфіка; авторська комунікативна стратегія; жанри канонічного типу; жанри неканонічного типу; poetological lyrics; specificity of the genre; author’s communicative strategy; genres of the canonical type; genres of the non-canonical type